Influence of Structural and Chemical Modification of Silica on its Surface Hydration - A.A. Turova; V.M. Gun'ko; V.V. Turov; P.P. Gorbik (Adsorption Science & Technology)
It was shown that an unusual structural type of water, which is weakly associated and unfrozen up to 180 K and possessing a proton resonance chemical shift at 1.5 ppm, appears at the patch-wise hydrophilic/hydrophobic interfaces of adsorbents placed in non-polar or weak solvents. Such water can amount to 10 wt% in amount.